Sensory evaluation, physicochemical properties and bioactivities of apis cerana honey with ginger - Chin, Hui Yee (2022)
There is a rise of consumer demand for a natural, healthy and saporous product, and this study presents the investigation on an innovative honey-based product which is ginger honey. The influence of ginger on the sensory quality of ginger honey in terms of visual, olfactory, taste, texture and acceptability were assessed. The physicochemical properties analyzed in this study were colour intensity, water activity, electrical conductivity, sugar content, moisture content, pH and reducing sugar content. The antioxidant capacities of the ginger honey were assessed using total phenolic content, iron chelating activity, superoxide anion radical scavenging activity and hydroxyl radical scavenging activity. Agar well diffusion assay was performed to evaluate the antibacterial activity of ginger honey. Generally, the addition of ginger increased woody, fresh, astringency and bitterness attributes but decreased sweetness, floral fresh fruit, warm, persistence and aftertaste attributes of the honey, however, the acceptability of ginger honey was reduced. Furthermore, the addition of ginger increased the colour intensity, moisture content, water activity, electrical conductivity, pH and reducing sugar content but decreased the total sugar content. Moreover, the addition of ginger had a significant contribution on the increment of total phenolic content, iron chelating activity, superoxide anion radical scavenging activity and hydroxyl radical scavenging activity of honey. Lastly, the ginger honey had a significant increment of antibacterial action on Enterococcus faecalis compared to the original honey. Contrarily, the ginger honeys did not cause significant increment of antibacterial effect against Pseudomonas aeruginosa. Overall, the addition of ginger had a negative impact on the overall acceptability due to altered aroma and taste attributes, caused changes on the physicochemical properties and enhanced the antioxidant capacities and antibacterial activities of honey.